Relationship between prostate cancer and type 2 diabetes mellitus - M. N. Peshkov; G. P. Peshkova; Igor V. Reshetov (Сахарный диабет)
Type 2 diabetes mellitus (DM2) and prostate cancer are widespread diseases throughout the world. Type II diabetes mellitus is accompanied by a deterioration in glycemic control, hyperinsulinemia, and insulin resistance (IR). The accumulation of glucose and lipids leads to a decrease in the density of insulin receptors and the development of insulin resistance in adipose tissue. This contributes to the development of hyperinsulinemia, which suppresses the breakdown of fat and leads to the progression of obesity. A vicious circle develops: insulin resistance → hyperinsulinemia → obesity → insulin resistance. Insulin influences the progression of the cell cycle, proliferation, and metastatic activity of the tumor.Recent studies have shown a strong direct correlation between fasting insulin levels and cancer mortality in men. This may be especially true in patients over 65, who are, in the first place, more likely to develop prostate cancer than younger patients. It should be noted that it is insulin, and not glucose, that is associated with the claim for the development of cancer. Hyperinsulinemia, which often occurs as a result of androgen deprivation therapy (ADT), the standard treatment for prostate cancer, is associated with a high tumor aggressiveness and faster treatment failure — the development of castrate-refractory prostate cancer. It is reasonable to assume that hyperinsulinemia — under whatever circumstances it is caused, whether due to ADT or due to inadequate nutrition and other lifestyle factors — can have the same negative effect on cellular signaling.Metabolic syndrome — essentially chronically elevated insulin levels — is closely associated with recurrence of cancer and worse post-treatment outcomes, which has led researchers to question generally accepted dietary guidelines for cancer patients, especially when they are undergoing treatment or recover from treatment, which may include recommendations to consume anything that will help maintain or restore body weight, regardless of sugar or carbohydrate content or its effect on insulin levels. A large number of patients live with hyperinsulinemia, but normoglycemia. Chronic hyperinsulinemia is the main driver of cardiometabolic disease, even when blood sugar levels are within reference values. The scale of this problem is not recognized by the medical and scientific community.